The Core Dimensions of Integrated Care: A Literature Review to Support the Development of a Comprehensive Framework for Implementing Integrated Care - González-Ortiz, Laura G. (Int J Integr Care, 2018)
OBJECTIVE: As part of the EU-funded Project INTEGRATE, the research sought to develop an evidence-based understanding of the key dimensions and items of integrated care associated with successful implementation across varying country contexts and relevant to different chronic and/or long-term conditions. This paper identifies the core dimensions of integrated care based on a review of previous literature on the topic. METHODOLOGY: The research reviewed literature evidence from the peer-reviewed and grey literature. It focused on reviewing research articles that had specifically developed frameworks on integrated care and/or set out key elements for successful implementation. The search initially focused on three main scientific journals and was limited to the period from 2006 to 2016. Then, the research snowballed the references from the selected published studies and engaged leading experts in the field to supplement the identification of relevant literature. Two investigators independently reviewed the selected articles using a standard data collection tool to gather the key elements analyzed in each article. RESULTS: A total of 710 articles were screened by title and abstract. Finally, 18 scientific contributions were selected, including studies from grey literature and experts’ suggestions. The analysis identified 175 items grouped in 12 categories. CONCLUSIONS: Most of the key factors reported in the literature derive from studies that developed their frameworks in specific contexts and/or for specific types of conditions. The identification and classification of the elements from this literature review provide a basis to develop a comprehensive framework enabling standardized descriptions and benchmarking of integrated care initiatives carried out in different contexts.